A prospective comparison of common toxicity criteria adverse events Version 3 and 4 in assessing oral mucositis for oral and oropharyngeal carcinoma. (March 2017) - Hickman, M.; Meade, S.J.; Fong, C.; Sanghera, P.; Good, J.; Hartley, A.
Highlights: There are frequent discrepancies between mucositis graded with Version 3 CTCAE and Version 4 CTCAE. Radiobiological modelling for mucositis has been based on systems assessing mucosal appearance. Version 3 and Version 4 CTCAE should both be used in future trials. Abstract: Background and purpose: Oral mucositis is an expected complication of radiotherapy in the management of carcinoma of the head and neck. The Common Terminology Criteria for Adverse Events (CTCAE) Version 3 (V3) and related systems based on mucosal appearance have been used in clinical trials historically. More recently, Version 4 (V4) which is based on patient symptoms has been employed. This study compares the use of V3 and V4 in the grading of mucositis in patients undergoing radiotherapy with or without concurrent systemic therapy for carcinoma of the oral cavity and oropharynx. Methods: Oral mucositis was graded prospectively in patients receiving radiotherapy with or without concurrent systemic therapy using both V3 and V4. Grading was recorded during and after completion of therapy. Results: Between November 2014 and November 2015, 555 measurements were taken from 73 patients. Mucositis scores were equal in both versions in 327 (59%) measurements. Significant differences between V3 and V4 were seen in patients receiving cetuximab-based concurrent therapy ( p < 0.001) and beyond 8 weeks from the start of radiotherapy ( p = 0.004). Conclusion: Differences in grading of mucositis scored by V3 and V4 are frequent. Relationships between biologically effective dose and rates of grade 3 mucositis have historically been based on mucosal appearances. It is not known whether the same relationships apply when mucositis is graded based on symptomatic grading systems. Both V3 and V4 should be used in clinical trials to improve understanding of mucositis and its relationship to quality of life and late mucosal toxicity.